Konflik Perebutan Lahan Parkir di Sekanak yang Memicu Bentrok antara Dinas Perhubungan dengan Sejumlah Kelompok - Syahrullah, RM (Indonesian Journal Publisher, 2023)
Fighting over parking spaces is certainly a familiar thing to hear because it happens very often in the city of Palembang, especially in the Sekkan area. Usually, phenomena like this occur due to clashing views, high levels of egoism, group fanaticism, lack of openness and, most importantly, lack of communication between parking attendants. The aim of this research is to find out how conflicts over parking spaces in childhood trigger clashes between the transportation service and a number of groups. The research method used is descriptive qualitative research, namely research that aims to describe or examine systematically, factually and accurately the facts, characteristics and relationships between the phenomena being investigated from the research object. The results of this research show that there is a conflict between parking attendants and the transportation service where there is a conflict over land which encourages cooperation between parking attendants. Other causal factors include economic needs, low education, social jealousy, lack of parking space, encouragement to usurp rights, and lack of attention from the government in parking management.